Microflora of boxes for holding veterinary patients in clinics - M. M. Mocherniuk; M. D. Kukhtyn; Y. V. Horiuk; V. V. Horiuk; O. A. Tsvigun; T. S. Tokarchuk (Regulatory Mechanisms in Biosystems, 2022)
A significant element of the prophylaxis of nosocomial infection in veterinary clinics is monitoring ambient objects, air, equipment, and instruments. In order to determine the role of boxes for keeping ill animals as a source of transmission of pathogens of nosocomial infections in veterinary clinics, we studied the microflora of surfaces of boxes and bioaerosol prior and after sanitation. For this purpose, we collected rinses from the surfaces of plastic and steel boxes, air samples prior to morning sanitation, after cleaning and wiping the surfaces with water and detergents and after disinfection. From the surfaces of the boxes for holding animals, we mostly isolated bacteria of Staphylococcus spp., Streptococcus spp., Micrococcus spp., Corynebacterium spp., Enterococcus spp. and Bacillus spp. Gram-negative species we found were bacteria of Escherichia spp., Acinetobacter spp. and Enterobacter spp. After wet cleaning and disinfection of plastic boxes, we detected species of Staphylococcus spp. and Enterococcus spp. in 5.4% of the samples, Micrococcus spp. in 8.1% and Bacillus spp. in 2.7%. Gram-negative bacteria of Enterobacter spp. were found in 2.7% of the samples. At the same time, the number of microorganisms in samples in which the bacteria were found after disinfection on the surfaces of stainless-steel boxes was 2.0 times lower than in such from the surfaces of plastic boxes. We determined that after wet disinfection of boxes’ surfaces, there occurred decrease in the microbial number in the air, equaling 3.7 times on average, compared with prior to disinfection. The basis of the air microflora after disinfection comprised species of Micrococcus spp., Corynebacterium spp. and Staphylococcus spp., which can be airborne-transmitted. Bacteria that were isolated from the boxes after disinfection (Micrococcus spp., Staphylococcus spp.) formed highly dense biofilms, which probably ensure the survival of the microbial cells, thus making the boxes a probable source of nosocomial infection.